Kemampuan Membaca Pemahaman Mahasiswa di Masa Pandemi - Toding Bua, Mety; Jhevraiyan Mangiri (Jurnal Elementaria Edukasia, 2023)
Reading proficiency among students during a pandemic demonstrated a lack of motivation in reading among students during online learning. Then, it is also absent in the observations made regarding the reader's comprehension of the text supplied during lectures. The offered reading took a lot of work for half of the 40 students to understand. The study aimed to describe the students in PGSD FKIP UBT's reading speed and reading comprehension of the reading material. Utilizing a qualitative approach, this investigation. The study's participants were 17 members of the 2019 batch of PGSD students, who were split up into different classrooms. This topic was picked because, as of July 2021, there were still pandemic conditions. The understanding test approach was employed in the data collection process. Based on the study's findings, information on students' reading comprehension and speed reading skills in the medium category was gathered. This is demonstrated by the typical student's reading comprehension score of 61%–70% and their speed reading score of 247.78 KPM, respectively. Based on the data collected, it can be said that the 2019 PGSD FKIP students do not have sufficient reading speed or comprehension because they are still unable to receive a score in the good group.